Revisiting SMEs’ Business Strategy: Shifting Outsourcing to Crowdsourcing Practices to Enhance SMEs’ Performance - Mansor, Mohd Fitri; Abu, Noor Hidayah; Abdul Halim, Hasliza; Ahmad, Noor Hazlina
The emergence of digital technology platforms such as crowdsourcing platform allows SMEs to establish an unmediated connection between suppliers and the customers; hence, enabling a close engagement with other stakeholders. Crowdsourcing practice offers the SMEs an unprecedented opportunity to enhance their business performance via the utilization of a large pool of crowds’ wisdom. Based on the above business strategy, it is very crucial to revisit SMEs’ business strategy; i.e., by shifting traditional method of conducting business (outsourcing) to new business phenomenon i.e. crowdsourcing practices. Specifically, this paper attempts to explore the roles of crowdsourcing practices, innovative owner-managers, and the relationship quality in enhancing SMEs’ business performance. The analysis technique used in this study using PLS-SEM. The study’s findings revealed that innovative owner-manager and relationship quality of commitment can be explained further via leveraging on crowdsourcing practices to improve business performance. This study may enrich the crowdsourcing knowledge among SMEs to revisit their existing business strategies; and to implement and better manage crowdsourcing practices in their organizations, particularly in sustaining their businesses post COVID-19